COVID-19 gone bad: A new character in the spectrum of the hyperferritinemic syndrome? - Colafrancesco, Serena (Autoimmun Rev, 2020)
The severe form of COVID-19 share several clinical and laboratory features with four entities gathered under the term “hyperferritinemic syndromes” and including macrophage activation syndrome (MAS), adult-onset Still's disease (AOSD), catastrophic anti-phospholipid syndrome (CAPS) and septic shock. COVID-19 systemic inflammatory reaction and “hyperferritinemic syndromes” are all characterized by high serum ferritin and a life-threatening hyper-inflammation sustained by a cytokines storm which eventually leads to multi-organ failure. In this review, we analyze the possible epidemiological and molecular mechanisms responsible for hyper-inflammation in patients with severe COVID-19 and we underline the similarities between this condition and “hyperferritinemic syndromes” which would allow considering severe COVID-19 as a fifth member of this spectrum of inflammatory conditions.